The effect of hyperosmolarity on fluid-phase and receptor-mediated endocytosis in P388D1 macrophages - Begg, Michael John (Division of Medical Biochemistry and Structural Biology, 2018)
Extracellular components can be internalized by either receptor-mediated or fluid-phase endocytosis. Receptor-mediated endocytosis involves the internalization of receptor-ligand complexes into coated vesicles of about 0.1 μm in diameter. The average diameter of primary pinocytic vesicles has been calculated to be 0.24 - 0.28 μm. The discrepancy in size between coated vesicles and the average pinosome diameter can be explained if, in addition to coated vesicles, another endocytic process involving vesicles larger than 0.28 μm in diameter takes place. These two vesicle types could together produce an average diameter of 0.24 μm. This hypothesis suggests that coated vesicles cannot fully account for fluid-phase uptake. Hypertonic conditions can selectively inhibit receptor-mediated endocytosis, leaving fluid-phase uptake unaffected, again suggesting that an alternative to coated pit-mediated uptake exists. In this study we determined the volume-weighted average diameter of primary pinocytic vesicles under hypertonic conditions (0.52 osm) where receptor-mediated uptake of transferrin was selectively inhibited by 42%. Fluid-phase uptake of FITC-dextran was unaffected by 0.52 osm medium. The internalization rate of ³H-galactose-labelled plasma membrane was reduced from 2.6 %/min to 1.5 %/min. The decrease in the rate of membrane internalization, without a reduction in the rate of fluid uptake at hypertonicity, implied a reduced surface to volume ratio of the pinocytic vesicles formed under these conditions. This suggested an increase in the average diameter of primary pinocytic vesicles. Membrane internalization rates were calculated on the assumption that all labelled cell-surface constituents were internalized to the same relative extent, as has been shown previously for isotonic conditions. This assumption was also shown to hold true under isotonic conditions. The reduced rate of membrane internalization under hypertonic conditions was shown not to be due to the exclusion of any labelled protein species from internalized vesicles. The larger average vesicle size determined under conditions of selective reduction of coated vesicle formation (i.e. hypertonicity), demonstrates the existence of a population of larger pinosomes involved in a possible alternative mechanism to coated-pit-mediated endocytosis.